Serum fibrinogen level in type 2 diabetes mellitus patients - Dhawale, Sanjay; Jayant, Satyam; Gupta, Anil Kumar (International Journal of Advances in Medicine, 2017)
Background: Diabetes mellitus is the most common metabolic disorder characterized by metabolic abnormalities and long term complications. The chronic complications of diabetes mellitus affect many organ systems and are responsible for the majority of morbidity and mortality associated with the disease. The aim of the study is to estimate the serum fibrinogen level in patients of Type 2 diabetes and correlate it with parameters like glycemic control (HbA1C), duration of diabetes mellitus, complications and pharmacotherapy. Methods: The study was conducted at the medicine department of J. A. Group of Hospital & G. R. Medical College, Gwalior, included patients of type-2 diabetes mellitus with or without microvascular complications between the ages of 25-85 years of either sex. Total 60 patients were selected randomly divided in two groups: Group A (n=34) was type-2 diabetes mellitus with microvascular complication, Group B (n=26) was type-2 diabetes mellitus without microvascular complication and Group C (n=28) was non diabetic healthy control. Patient’s history, clinical examination, routine blood tests, serum fibrinogen level and fundus examination were carried out. Serum fibrinogen was measured by Clauss method. Results: Maximum number of patients in study was between 40-60 years’ age group. Microvascular complication in Group A were nephropathy (n=17), retinopathy (n=13) and neuropathy (n=4). Serum fibrinogen level in patient with microvascular complications, without microvascular complications and in non-diabetic controls were 515±138.7, 437±137 and 308±52.65 respectively. Serum fibrinogen level was higher in overweight patients as compared to normal weight patient in all groups. Serum fibrinogen level in different albuminuria groups (<30mg/l, 30-300mg/l, >300mg/l) were 439.7±135.15, 525.7±145.4, 545.7±112.2 respectively. Mean fibrinogen level was 541.1±121.7 in diabetics with total cholesterol >200. Serum fibrinogen level in patients with HbA1C >12% among both group A & B was 567.5±173.4 and 538.6±184.6 respectively. Most of type-2 diabetes mellitus patient have high fasting blood sugar >126 and high PPBS >200 in both group A & B. Mean fibrinogen level in patients taking insulin, oral hypoglycemic agents and in patients who were not taking any treatment was 640.8±126.4, 449.9±145.7, 419±72 respectively. Conclusions: Further larger studies are required studying the serum fibrinogen level in diabetic patients with microvascular complications and effect of interventions done to reduce the fibrinogen levels.